High Mortality Rate in Adult COVID-19 Inpatients in Eastern Sudan: A Retrospective Study - Omar,Saeed; Musa,Imad; Salah,Sami; Elnur,Mohammed; Al-Wutayd,Osama; Adam,Ishag (Journal of Multidisciplinary Healthcare, 2020)
Saeed M Omar,1 Imad R Musa,2 Sami E Salah,1 Mohammed M Elnur,1 Osama Al-Wutayd,3 Ishag Adam4 1Department of Medicine, Faculty of Medicine, Gadarif University, Gadarif, Sudan; 2Department of Medicine, Royal Commission Hospital at AL Jubail Industrial City, Al Jubail, Kingdom of Saudi Arabia; 3Department of Family and Community Medicine, Unaizah College of Medicine and Medical Sciences, Qassim University, Unaizah, Kingdom of Saudi Arabia; 4Department of Obstetrics and Gynecology, Unaizah College of Medicine and Medical Sciences, Qassim University, Unaizah, Kingdom of Saudi ArabiaCorrespondence: Osama Al-WutaydDepartment of Family and Community Medicine, Unaizah College of Medicine and Medical Sciences, Qassim University, P.O. Box 991, Unaizah, Qassim 51911, Kingdom of Saudi ArabiaEmail o.alwutayd@qu.edu.saIshag AdamDepartment of Obstetrics and Gynecology, Unaizah College of Medicine and Medical Sciences, Qassim University P.O. Box 991, Unaizah, Qassim 51911, Kingdom of Saudi ArabiaEmail ishagadam@hotmail.comAim: The current pandemic of coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory coronavirus syndrome 2 (SARS-CoV-2). It is a global public health concern that has resulted in the rapid growth in the number of infected patients with significant mortality rates. Hence, we conducted a retrospective study in Gadarif Hospital to evaluate the presenting manifestations, mortality rate, and the risk factors associated with mortality in hospitalized patients.Methods: A retrospective study was conducted at Gadarif Hospital in Eastern Sudan. Medical files of the patients admitted during the period between April and July 2020 were reviewed. All the files of the adult patients (aged 18 or above), of both sexes, who had a confirmed COVID-19-positive status via laboratory testing using PCR and who were admitted during this period were reviewed. The data extracted included patients’ demographics and initial clinical presentation, symptoms, signs, and the laboratory and radiographic findings. The data ...